The common African lexical core of the Upper Guinea Creoles and its historical significance - (:unkn) unknown (My University, 2019)
In this paper, we scrutinize and compare the African lexical elements shared by several varieties of Upper Guinea Portuguese Creoles, belonging to the three branches of this group: (i) Continental (Bissau, Cacheu, Casamance, and Geba), (ii) Insular (Fogo and Santiago), and (iii) ABC islands (Curaçao). This is the first study to provide comparative data for a wide range of different creoles of this group. The comparison is based on a standard list of 96 African-derived terms attested in Santiago Capeverdean Creole and builds on three main comparative criteria: (i) presence/absence of a given African-derived term, (ii) phonetic similarity and (iii) semantic similarity. The results show how these items help us understand better (i) which African languages were the main contributors to the formation of the early Upper Guinea Proto-Creole that must have been spoken around the turn of the 15th and 16th centuries, as well as (ii) the historical and phylogenetic relationships existing between the various Upper Guinea Portuguese Creoles at stake. Particularly worthy of mention is the examination of the African element in Fogo Capeverdean and the considerations about the internal classification of the Continental branch of this group of creoles.
Keywords: African Research